Tabellio, Notarius, Notaio: quale funzione? Una vicenda bimillenaria - Bassani, Alessandra; Pulitanò, Francesca (Milano University Press, 2022)
The book is part of the multidisciplinary research project Languages ​​of notarial mediation from the Middle Ages to the Modern Age (LIMEN) of the University of Milan. It collects the point of view of jurists: it is a journey through time, which ranges from the origins of the notarial function to the exercise of it in our time. The book highlights the evolution of the role of the notary in different ages and cultural contexts, a role which has always guaranteed trust and impartiality in the drafting and conservation of legal documents. The collection offers a 'evolving' representation of the tasks of notaries, starting from the assumption that the recovery of historical, legal and cultural roots can provide a key for the understanding of today's profession as well as some points of reflection for the future.